Penerapan Sistem Informasi Akuntansi Persediaan Bahan Baku Terhadap Produktivitas Produksi Pada PT Sumber Mitra Sejati Jaya - Pramiudi, Udi; Supardji, Supardji; Br Ginting, Ruth Natalia (Institut Bisnis dan Informatika Kesatuan, 2015)
The purpose of this research is to evaluate the application of accounting infomation system of raw mateHal inventories„ and the application of raw materials inventories and how they affect productivity. The result indicated that most of the application information system of raw material inventory has been properly applied and overall adequate for the benefit ofthe company. This is seen from accounting infomation system of raw materials components and the procedures perfonned are all in accordance to standard operational prosedure (SOP) applied by the company. The standard of productivity was targeted at 95%. The average percentage of snack productivity in 2013 is 92,53%, wheat production 94,93%, crackers production 96,17%, and chili production 97,53%. Keywords: Accounting Infomation Systems Raw Materials Inventory , Productivity.